Systematic analysis of the caridean shrimp superfamily Pandaloidea (Crustacea: Decapoda) based on molecular and morphological evidence - Liao, Y; Ma, K; De Grave, S; Komai, T; Chan, T; Chu, K (Elsevier, 2019)
One of the systematically controversial superfamilies in Caridea is the predominately deep-sea or cold water Pandaloidea, largely because this species-rich group of nearly 200 species in 25 genera exhibits a very high diversity of body forms and ecology. Although the relationships amongst the taxa within Pandaloidea have been repeatedly discussed based on morphology, no comprehensive molecular phylogeny exists. In this study, we present the first molecular phylogeny of the group, based on a combined dataset of two mitochondrial (12S and 16S rRNA) and six nuclear (ATP synthase β-subunit, enolase, glyceraldehyde-3-phosphate dehydrogenase, histone 3, phosphoenolpyruvate carboxykinase and sodium–potassium ATPase α-subunit) markers, based on 62 species (about 1/3 of known biodiversity) in 22 genera (88% of genera) of two pandaloid families (Pandalidae, Thalassocarididae) and outgroups from seven other caridean families. With generally high support, the relationships within the clade are fully resolved. Pandalidae is shown to be paraphyletic with Thalassocarididae deeply nested within as a monophyletic group, and the latter is herein considered to be a synonym of Pandalidae. Five major clades are recovered, with the shallow water genera Anachlorocurtis, Chlorocurtis, Chlorotocella and Miropandalus forming a sister clade to the remaining genera. At the genus level, the phylogeny indicates Plesionika, Heterocarpus and Pandalus to be not monophyletic. The validity of Pandalopsis, Stylopandalus and Calipandalus is challenged and these genera are considered herein to be junior synonyms of Pandalus (Pandalopsis) and Plesionika (Stylopandalus and Calipandalus). Although not fully resolved, some evidence potentially considers Nothocaris to be a valid genus. Ancestral State Reconstruction successfully recovered 15 synapomorphies for the major clades, with 11 of them reported to be of systematic significance for the first time.